On Finsler Σ-spaces - D. Latifi; M. Toomanian (Հայաստանի ԳԱԱ)
In this paper, we study Finsler Σ-space. We first prove that any Σ-space is a homogeneous Finsler space. Then we study some geometric properties of Berwald Σ-space and prove that any generalized symmetric Berwald space is a Berwald Σ-space where Σ is cyclic.
Keywords: Mathematics; Science